Free Radicals and Diseases 2016
DOI: 10.5772/64708
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Free Radicals in the Development and Progression of Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is a major dementia related to an overproduction of free radicals (FRs), which leads to the generation of oxidative stress in brain tissue. Amyloid beta-peptide of 42 amino acid residues (Aβ 1-42) is the main source of FRs in patients with AD. βA 1-42 results from hydrolysis of the amyloid precursor protein by β-secretase in a process known as the amyloidogenic pathway. During βA 1-42 aggregation, the peptide interacts with various transition metals to produce hydrogen peroxide (H 2 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 100 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…Other AD-related research show that group I mGluRs can control APP metabolism and hasten the conversion of APP into non-amyloidogenic APP( Chong et al, 2003 ). Additionally, it has been demonstrated that group III mGluR activation shields neurons from microglial neurotoxicity when Aβ is applied, which may be caused by the control of caspase activity( Hernández et al, 2016 );( Chong et al, 2005 ); ( Lin et al, 2001 ).…”
Section: Drug Targets In Admentioning
confidence: 99%
“…Other AD-related research show that group I mGluRs can control APP metabolism and hasten the conversion of APP into non-amyloidogenic APP( Chong et al, 2003 ). Additionally, it has been demonstrated that group III mGluR activation shields neurons from microglial neurotoxicity when Aβ is applied, which may be caused by the control of caspase activity( Hernández et al, 2016 );( Chong et al, 2005 ); ( Lin et al, 2001 ).…”
Section: Drug Targets In Admentioning
confidence: 99%